2023
DOI: 10.3390/buildings13122948
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Micro- and Nano-Dispersion Additives for Asphalt and Bitumen for Road Construction

Kinga Korniejenko,
Marek Nykiel,
Marta Choinska
et al.

Abstract: The main motivations for the development of research in the area of appropriate additives for asphalt and bitumen are the enhancement of their properties and improvement of their production process, including the reduction in environmental burden. Many additives improve the properties of mineral–asphalt mixtures. Traditionally, additives such as the following are applied: elastomers, plastomers, latexes, rubber powder, resins, and others. Currently, the modification of asphalt and bitumen materials by traditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 137 publications
0
3
0
Order By: Relevance
“…They showed that thanks to the application of PCM it is possible to reduce heating demand, enhance thermal comfort, and better utilize solar energy through effective storage [7]. The investigation in this area supports the development of PCMs in pavement applications [43].…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…They showed that thanks to the application of PCM it is possible to reduce heating demand, enhance thermal comfort, and better utilize solar energy through effective storage [7]. The investigation in this area supports the development of PCMs in pavement applications [43].…”
mentioning
confidence: 73%
“…Today, the usage of PCM in the road industry can seem to be not economically justified, because the road industry is focused on cost minimization. However, taking into consideration wider perspectives, including the cost of maintenance and the reduction in the number of potential accidents in the long term, this investment can be beneficial [43].…”
Section: Further Perspectivesmentioning
confidence: 99%
“…Consequently, the maintenance and repair of such pavement failures become costly [1]. In an effort to prevent failures and achieve more cost-effective pavements, numerous methods have been developed to enhance the performance and extend the service life of flexible pavements [2][3][4][5][6]. One of the most effective methods is the modification of asphalt with various additive materials to improve the virgin asphalt cement's performance characteristics.…”
Section: Introductionmentioning
confidence: 99%